Pengaruh Biaya Produksi, Biaya Operasional dan Penjualan Terhadap Laba Bersih Pata Perusahaan Sektor Industri Dasar dan Kimia di Bursa Efek Indonesia Tahun 2020-2024 - Lestari, Anggi Putri; Yudi, Yudi; Yuliusman, Yuliusman (Jambi Accounting Review (JAR), 2025)
This study aims to determine the Effect of Production Costs, Operating Costs and Sales on Net Profit in Basic Industry and Chemical Sector Companies Listed on the Indonesia Stock Exchange in 2020-2024. This type of research is quantitative research with an associative approach. The population in this study amounted to 73 companies and a sample of 35 companies was obtained using a purposive sampling technique. The data collection method used the exchange rate and documentation method. The data analysis techniques used were descriptive statistical tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression analysis, t-tests, f-tests and coefficient of determination (R2) tests. The simultaneous coefficient of determination is 69.8%, and the remaining 30.2% is influenced by other variables not explained in this study.